Systematic Review of Non-ASCP Choosing Wisely Recommendations Relevant to Pathology and Laboratory Medicine. Issue 3 (7th February 2018) - Waibel, Elizabeth; Garcia, Edna; Kelly, Melissa; Soles, Ryan; Hilborne, Lee
Abstract: Objectives: To determine non–American Society for Clinical Pathology pathology- and laboratory-related Choosing Wisely recommendations that drive effective test utilization in the laboratory. Methods: Data were collected via a two-part web-based survey distributed to a broad sample of pathologists and laboratory professionals from a variety of institutions. Results: Pathologists' most relevant recommendation: "Do not transfuse more units of blood than absolutely necessary"; highest priority: "Do not transfuse more than the minimum number of RBC units necessary to relieve symptoms of anemia or to return a patient to a safe hemoglobin range (7-8 g/dL in stable, noncardiac inpatients)." Laboratory professionals' most relevant recommendation: "Avoid testing for a Clostridium difficile infection in the absence of diarrhea"; highest priority: "Do not routinely transfuse stable, asymptomatic hospitalized patients with a hemoglobin level greater than 7 to 8 g/dL." Conclusions: Most of the highest priority, most relevant recommendations among those surveyed concerned utilization of blood products and transfusion management.